Development and Construct Validation of Service-Learning Civic Competency Scale in Pakistani Context - Dr. Iqbal Ahmad; Dr. Farah Deeba; Dr. Muhammad Aqeel Raza (Research Journal of Psychology, 2025)
One of the major aims of education is to prepare civically active and responsible citizens for future societies. Service-learning has always been instrumental to achieve this goal. Several instruments have been developed and used to measure service-learning outcomes all over the world. However, the absence of a valid instrument has always made it difficult for educators and management to measure contributions of service-learning for civic competencies of students in Pakistani context. This study aimed to develop and validate an instrument for measuring civic competencies of students as a result of participating in service-learning activity. The instrument was developed based on literature review on civic competencies and service-learning. The theoretical foundation for the development of the civic competency scale was derived from the works of Lambright and Lu (2010). An instrument consisting of 21 items was constructed to measure the four domains of civic competencies among students such as civic knowledge, civic skills, civic commitment and civic values. Data were collected from 314 students from 3 private colleges in district Chitral of Khyber Pakhtunkhwa, Pakistan who participated in a service-learning activity as part of their academic course. The exploratory and confirmatory factor analysis provided strong evidences regarding reliability and validity of the newly constructed scale. It is concluded that SLCCS is a reliable and valid instrument for measuring civic competencies of students participating in service-learning. It is suggested that the instrument may be used retested in other contexts for further validation proofs.